Ação pública na formação e transformação do destino turístico de Porto de Galinhas: um estudo dos referenciais no período de 1970 a 2010 - Lopes, Alba de Oliveira Barbosa (2014)
The central interest of this thesis is to comprehend how the public action impels the formation and transformation of the tourist destinies. The research was based on the premise that the public actions are the result of the mediation process of state and non-state actors considered important in a section, which interact aiming for prevailing their interests and world visions above the others. The case of Porto de Galinhas beach, in Pernambuco, locus of the investigation of this thesis, allowed the analysis of a multiplicity of actors on the formation and implementation of local actions toward the development of the tourism between the years 1970 and 2010, as well as permitted the comprehension of the construction of the referential on the interventions made. This thesis, of a qualitative nature, has as theoretical support the cognitive approach of analysis of the public policies developed in France, and it has as main exponents the authors Bruno Jobert and Pierre Muller. This choice was made by the emphasis on the cognitive and normative factors of the politics, which aspects are not very explored in the studies of public policies in Brazil. As the source of the data collection, documental, bibliographic and field researches were utilized to the (re)constitution of the formation and transformation in the site concerned. The analysis techniques applied were the content and the documental analysis. To trace the public action referential, it started by the characterization of the touristic section frontiers and the creation of images by the main international body: the World Tourism Organization, of which analysis of the minutes of the meetings underscored guidelines to the member countries, including Brazil, which compounds the global-sectorial reference of the section. As from the analysis of the evolution of the tourism in the country, was identified that public policies in Brazil passed by transformations in their organization over the years, indicating changes in the referential that guided the interventions. These guidelines and transformations were identified in the construction of the tourist destination of Porto de Galinhas, of which data was systematized and presented in four historical periods, in which were discussed the values, the standard, the algorithms, the images and the important mediators. It has been revealed that the State worked in different roles in the decades analyzed in local tourism. From the 1990s, however, new actors were inserted in the formulation and implementation of policies developed, especially for local hotelkeepers. These, through their association, establishes a leadership relation in the local touristic section, thereby, they could set their hegemony and spread their own interest. The leadership acquired by a group of actors, in the case of Porto de Galinhas, does not mean that trade within the industry were neutralized, but that there is a cognitive framework that confronts the actors involved. In spite of the advances achieved by the work of the mediators in the last decades, that resulted in an amplification and diversification of the activity in the area, as well as the consolidation at the beach, as a tourist destiny of national standout, the position of the place is instable, concerned to the competitiveness, once that there is an situation of social and environmental unsustainability